2009
DOI: 10.1152/physiolgenomics.90323.2008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the hibernation cycle using LC-MS-based metabolomics in ground squirrel liver

Abstract: A hallmark of hibernation in mammals is metabolic flexibility, which is typified by reversible bouts of metabolic depression (torpor) and the seasonal shift from predominantly carbohydrate to lipid metabolism from summer to winter. To provide new insight into the control and consequences of hibernation, we used LC/MS-based metabolomics to measure differences in small molecules in ground squirrel liver in five activity states: summer, entering torpor, late torpor, arousing from torpor, and interbout arousal. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
45
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 61 publications
7
45
0
Order By: Relevance
“…I predicted that the addition of carnitine would facilitate fatty acyl CoAs transported to the matrix, relieving any accumulation of fatty acyl CoAs in the IMS that might inhibit the DCT and, as a result, succinate transport would resume and respiration would increase (figure 1.4). This prediction was further supported by the work of Nelson et al (2009) who found carnitine concentrations in liver tissue to be higher in arousing and IBE animals, but low in torpid hibernators. However as their work was performed in homogenized liver tissue (Nelson et al, 2009), I am unable to distinguish whether these higher carnitine concentrations in IBE occur in the mitochondria or in the cytosol.…”
Section: Coa Treated Mitochondriasupporting
confidence: 55%
See 2 more Smart Citations
“…I predicted that the addition of carnitine would facilitate fatty acyl CoAs transported to the matrix, relieving any accumulation of fatty acyl CoAs in the IMS that might inhibit the DCT and, as a result, succinate transport would resume and respiration would increase (figure 1.4). This prediction was further supported by the work of Nelson et al (2009) who found carnitine concentrations in liver tissue to be higher in arousing and IBE animals, but low in torpid hibernators. However as their work was performed in homogenized liver tissue (Nelson et al, 2009), I am unable to distinguish whether these higher carnitine concentrations in IBE occur in the mitochondria or in the cytosol.…”
Section: Coa Treated Mitochondriasupporting
confidence: 55%
“…This prediction was further supported by the work of Nelson et al (2009) who found carnitine concentrations in liver tissue to be higher in arousing and IBE animals, but low in torpid hibernators. However as their work was performed in homogenized liver tissue (Nelson et al, 2009), I am unable to distinguish whether these higher carnitine concentrations in IBE occur in the mitochondria or in the cytosol.…”
Section: Coa Treated Mitochondriasupporting
confidence: 55%
See 1 more Smart Citation
“…Biliverdin and bilirubin are heme catabolites, and all three compounds have been implicated in redox regulation (35), riboflavin primarily in the context of fatty acid oxidation (20). It appears likely that they are taken up rapidly by other tissues, including liver which demonstrated a perfectly reciprocal pattern of both flavin and biliverdin levels in the same species (32). Similar to our results, bilirubin was found elevated during torpor in plasma in jerboas (30) and in bile of torpid goldenmantled ground squirrel (4).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work to measure metabolite changes in hibernators documents a number of alterations in liver (2,32,36), brain (21,40), brown adipose tissue (13), bile (4), and blood (1,9,24,31) that begin to assess the metabolites cycling in association with hibernation. These data suggest a two-switch model for the circannual rhythm of hibernation whereby the torporarousal cycle is temporally segregated from the summer-winter cycle such that torpor-arousal occurs only in winter (36).…”
mentioning
confidence: 99%